Comparison of two interferon-gamma release assays (QuantiFERON-TB Gold In-Tube and T-SPOT.TB) in testing for latent tuberculosis infection among HIV-infected adults. (October 2013) - Sultan, B; Benn, P; Mahungu, T; Young, M; Mercey, D; Morris-Jones, S; Miller, RF
There is currently no 'gold standard' for diagnosis of latent tuberculosis infection (LTBI), and both the tuberculin skin test and interferon-gamma release assays (IGRAs) are used for diagnosis; the latter have a higher sensitivity than tuberculin skin tests for diagnosis of LTBI in HIV-infected individuals with lower CD4 counts. No evidence base exists for selection of IGRA methodology to identify LTBI among human immunodeficiency virus-infected patients in the UK. We prospectively evaluated two commercially available IGRA methods (QuantiFERON-TB Gold In Tube [QFG] and T-SPOT.TB) for testing LTBI among HIV-infected patients potentially nosocomially exposed to an HIV-infected patient with 'smear-positive' pulmonary tuberculosis. Among the exposed patients median CD4 count was 550 cells/µL; 105 (90%) of 117 were receiving antiretroviral therapy, of who 104 (99%) had an undetectable plasma HIV load. IGRAs were positive in 12 patients (10.3%); QFG positive in 11 (9.4%) and T-SPOT.TB positive in six (5.1%); both IGRAs were positive in five patients (4.3%). There was one indeterminate QFG and one borderline T-SPOT.TB result. Concordance between the two IGRAs was moderate ( κ = 0.56, 95% confidence interval = 0.27–0.85). IGRAs were positive in only 4 (29%) of 14 patients with previous culture-proven tuberculosis. No patient developed tuberculosis during 20 months of follow-up.